Community owned trading enterprises : their uniqueness and performance : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Business Studies at Massey University - Teahan, B. J (Massey University, 2000)
Community ownership of trading enterprises has not been so favoured as a concept during the latter part of the 20th century as successive New Zealand Governments pursued market forces policies. The face of the New Zealand public ownership business scene radically changed from the mid 1980's as telecommunications, railways, the ports, Coal Corp, energy ... were all restructured in pursuit of the market model. Why was the public or community ownership model apparently not supported? The empirical evidence did not unequivocally uphold privatisation and the market model as being inherently more efficient as a structure. Notably also, community ownership was much enjoyed as a concept. This research, therefore, looks at the concept of community ownership and seeks to define its uniqueness and identify its performance in operating trading enterprises. The electricity companies in New Zealand were the area selected. The results moderately support the view that social/community goals are of more importance to community owned trading enterprises than their private ownership equivalents. Notably community ownership outperformed private enterprise as measured by ROE and ROA. Thus the contention that community ownership as a concept had much to offer, and was not inherently less efficient, was not disproved by this research. Further research in other fields is worthy of pursuit.
Keywords: New Zealand; Government business enterprises; Corporations, Government; Electric utilities -- Deregulation